2006
DOI: 10.4142/jvs.2006.7.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake of magnetic nanoparticle is mediated through energy-dependent endocytosis in A549 cells

Abstract: Biocompatible silica-overcoated magnetic nanoparticles containing an organic fluorescence dye, rhodamine B isothiocyanate (RITC), within a silica shell [50 nm size, MNP@SiO2(RITC)s] were synthesized. For future application of the MNP@SiO2(RITC)s into diverse areas of research such as drug or gene delivery, bioimaging, and biosensors, detailed information of the cellular uptake process of the nanoparticles is essential. Thus, this study was performed to elucidate the precise mechanism by which the lung cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
105
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(113 citation statements)
references
References 18 publications
8
105
0
Order By: Relevance
“…Suppression of MNPs uptake into A549 cell at low temperature has observed also Kim et al [7]. It is supposed that the particle size determines the mechanism of nanoparticle entrance into cells [40].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Suppression of MNPs uptake into A549 cell at low temperature has observed also Kim et al [7]. It is supposed that the particle size determines the mechanism of nanoparticle entrance into cells [40].…”
Section: Discussionmentioning
confidence: 75%
“…However, the data published so far lack concordance about the threshold diameter which determines the particular endocytotic pathway involved in particle internalization [41]. Using the specific metabolic inhibitors it has been shown that magnetite nanoparticles of the hydrodynamic size around 80 nm are internalized by clathrin-mediated endocytosis [7,42]. Further experiments are required to determine the precise mechanism(s) of cellular uptake of particular coated MNPs used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most work to date evaluating cellular MP uptake and handling has utilized cell lines [34][35][36][37][38]. This risks chronic contamination by mycoplasma -such 'cryptic' contamination can alter cell structure, metabolism and growth, all of which can impact the interpretation of data [42].…”
Section: Discussionmentioning
confidence: 99%
“…This endocytic process can be significantly influenced by temperature and blocked by the endocytosis inhibitor NaN 3 . 38 It is demonstrated in both our current and previous studies that the uptake of Tet-NPs is mainly mediated by endocytosis, a kind of transportation mechanism which is more efficient than the cellular uptake of free drug by filtration, thereby leading to the enhanced cytotoxicity of Tet-NPs. 25 …”
mentioning
confidence: 99%